Integrated Sustainable Agriculture to Realize Biodiversity-Based Food and Energy Sovereignty - Bambang Pujiasmanto; Desy Setyaningrum (Journal of Biodiversity and Biotechnology, 2022)
Sustainable agriculture is the management and conservation of natural resources, oriented to technological and institutional changes carried out in such a way as to ensure the fulfillment and satisfaction of human needs in a sustainable manner for present and future generations. Food independence is the ability of the state and nation to produce diverse food from within the country which can ensure the fulfillment of sufficient food needs. Basically the food must be available at all times and to be able to meet the criteria for food security. Food availability is determined by 3 main aspects, namely production (quantity), distribution (accessibility), and consumption (nutritious and safe). In addition, renewable energy can come from agricultural materials. The energy crisis that occurs today is caused by an imbalance in the demand for energy that continues to increase with energy supply that is dependent on non-renewable fossil fuels, such as oil, coal and natural gas. This dependence is a serious threat to the world because of the known depletion of petroleum reserves, the instability of oil prices, and the pollution of greenhouse gases due to the burning of fossil fuels. The energy crisis will result in losses, both material and immaterial, such as loss of investor and consumer confidence, hampered creativity, inefficiency, and the risk of social unrest. The solution that is usually offered to overcome the energy crisis that occurs is the development and use of alternative energy sources, one of which is biofuels or biofuels.